The impact of private capital flows on economic growth in the MENA region - Ben-Salha, Ousama; Zmami, Mourad (Economics and Business Review, 2020)
The aim of the article is to conduct an empirical analysis of the impact ofaggregate and disaggregate private capital flows on economic growth in eleven MENAcountries between 1980 and 2018. Unlike prior empirical studies, the fixed effect panelquantile approach developed by Canay (2011) is implemented. Findings suggestthat there is a significant difference in the effects of private capital flows on economicgrowth across lower and higher quantiles. More specifically, the effects of total privatecapital flows, foreign direct investment flows, portfolio flows and debt flows are positiveand statistically significant only for low and medium quantiles, indicating thatthe enhancing impact of private capital flows in terms of economic growth is onlyconfirmed in countries with relatively low and medium growth rates. Moreover, debtflows affect economic growth in countries recording high growth rates, stressing theimportance of financial development in routing those flows into the most productiveprojects in the economy.